2012
DOI: 10.1128/jvi.01501-12
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Host Genes Directed by Virus-Derived Short Interfering RNAs in Caenorhabditis elegans

Abstract: bSmall interfering RNAs (siRNAs) processed from viral replication intermediates by RNase III-like enzyme Dicer guide sequence-specific antiviral silencing in fungi, plants, and invertebrates. In plants, virus-derived siRNAs (viRNAs) can target and silence cellular transcripts and, in some cases, are responsible for the induction of plant diseases. Currently it remains unclear whether viRNAs are also capable of modulating the expression of cellular genes in the animal kingdom, although animal virus-encoded micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 52 publications
(72 reference statements)
3
38
0
Order By: Relevance
“…Total RNA extraction, small RNA enrichment, detection of viral and cellular transcripts, and small RNAs were carried out following protocols described previously (43,46). DNA oligos with sequence ATTGCCGTACTGAACGATCTCA were labeled and used for the detection of miR-58.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA extraction, small RNA enrichment, detection of viral and cellular transcripts, and small RNAs were carried out following protocols described previously (43,46). DNA oligos with sequence ATTGCCGTACTGAACGATCTCA were labeled and used for the detection of miR-58.…”
Section: Methodsmentioning
confidence: 99%
“…S8). Our recent study has detected RNAi of cellular mRNAs targeted by virus-derived siRNAs in C. elegans (43). Because low levels of FR1gfp-derived viral siRNAs remained detectable in drh-1 mutants (Fig.…”
Section: The Helicase and Ctd Domains Of Rig-i Were Functional In A Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Small RNAs targeting viral genomes (viRNA) accumulate in wild type infected worms, but not mutant worms [35,36]. Moreover, it was shown that viRNAs are capable of being transmitted between generations of worms [21,24]. RNAi heterozygous mutant worms, which are functionally competent, can generate anti-viral RNAi immunity that protects their homozygous RNAi-mutant progeny from replication of a transgenic Flock House Virus (FHV) for multiple generations [21].…”
Section: Inherited Anti-viral Immunitymentioning
confidence: 99%
“…Each nematode produces hundreds of progeny, and therefore small RNAs must be amplified to overcome the transgenerational dilution effect that expands logarithmically. Indeed, in worms which are mutants for the RdRP RRF-1, inherited RNAi diminishes after 2 generations, indicating the RNA amplification is required for long-term transgenerational RNAi effects [21,24]. In addition, it was recently demonstrated that the RRF-1 RdRP is required for effective transgenerational targeting of chromatin [25].…”
mentioning
confidence: 99%